Analysis of eye tracking data applied to Autism Spectrum Disorder during virtual reality experiments - Paz, Maria da Paz Olímpio Lardosa (2019)
Dissertação de Mestrado Integrado em Engenharia Biomédica apresentada à Faculdade de Ciências e Tecnologia